A humanised therapeutic CD4 mAb inhibits TCR-induced IL-2, IL-4, and IL-10 secretion and expression of CD25, CD40L, and CD69. - Woods, M; Guy, R; Waldmann, H; Glennie, M; Alexander, DR (1998)
The actions of a humanised therapeutic CD4 mAb YHB.46 on T cell activation were investigated in vitro. Soluble YHB.46 IgG or YHB.46-derived F(ab')2 fragments caused inhibitions of up to 100% of the proliferation of purified CD4+ T cells activated with immobilised CD3 mAb. The inhibitory effects of the CD4 mAb were equally potent in both CD45RA+ and CD45RO+ T cell subset proliferation assays. Inhibitory effects on DNA synthesis were nto explicable by increased T cell apoptosis. YHB.46 was inhibitory even when added 70 h after exposure of cells to immobilised CD3 mAb, but it had little effect on IL-2 receptor-driven proliferation signals. The CD4 mAb inhibited the CD3-induced expression of the CD25 and CD69 activation markers on the T cell surface and suppressed CD40 ligand expression, but not that of CD25 and CD69, when their expression was induced by phorbol ester plus ionomycin. YHB.46 also exerted a profound inhibitory effect on the production of IL-2, IL-4, and IL-10, irrespective of whether T cells were activated with CD3 mAb or with phorbol ester plus ionomycin. The inhibitory effects of YHB.46 on CD4+ T cell proliferation were partially prevented by the addition of exogenous IL-2 or autologous monocytes and were completely prevented by activating T cells with a novel CD3-CD28 bivalent F(ab')2 reagent. However, the inhibitory effects of YHB.46 on T cell proliferation were equipotent in the presence or the absence of CTLA-4Ig, showing that the CD4 mAb was not acting on CD28-induced activation signals per se. Our results show that the inhibitory effects of YHB.46 on T cell activation do not involve CD28 or IL-2 receptor signalling, but are directed at the TCR-mediated G0-G1 transition. These findings in vitro predict that YHB.46 may act as a potent immunosuppressant in the clinical context.